ON STRONG AND WEAK CONVERGENCE IN n-HILBERT SPACES - Soenjaya, Agus L. (IndoMS, 2013)
We discuss the concepts of strong and weak convergence in n-Hilbert spaces and study their properties. Some examples are given to illustrate the concepts. In particular, we prove an analogue of Banach-Saks-Mazur theorem and Radon-Riesz property in the case of n-Hilbert space.DOI :Â http://dx.doi.org/10.22342/jims.19.2.164.79-87